Optimal Decisions and Pricing in Mail Service Systems Subject to Virus Attacks - Sheng Zhu; Jinting Wang (Complexity)
We consider an optimal decision problem of the service providers in public mail service systems subject to virus attacks. Two scenarios, i.e., free service systems and payment systems, are investigated in the paper. We first formulate the considered system as a partially observable M/G/1 queue with Bernoulli vacations, and by the supplementary variable method, we obtain some performance measures of the system. In the case of free service systems, the service provider aims to maximize the expected social welfare. Correspondingly, we obtain a joint optimum value of scan rate and scan probability from the viewpoint of social welfare maximization and carry out a sensitivity analysis of the joint optimum value on some input parameters. In the case of payment systems, senders are assumed to be boundedly rational, and we obtain a three-dimensional (3D) optimal strategy by combining the Stackelberg game approach and the logit choice model. Our results provide managerial insight and are helpful for service providers to optimally select parameters of the system and make optimal pricing decisions in various situations.